Images, iconoclasm, and the Carolingians - Noble, Thomas F. X. (Middle Ages series., 2009)
Noble (Notre Dame) has produced a very useful work that will change the way iconoclasm is taught. The book's first half is dedicated to an investigation of late antique and Byzantine images and thoughts about them. It seems not to have been an issue of great concern. The devotional and liturgical use of images, Noble argues, was a recent development by the time of Emperor Leo III's iconoclasm. Chapter 4 is very useful as a study of the Opus Caroli regis contra synodum, formerly known as the Libri Carolini. Carolingian scholars, especially Theodulf, are seen here in perfect command of Byzantine theological concepts. They were not the ignorant bumpkins most have held them to be. Chapters 5-7 constitute a study of the controversy over images in the Carolingian world from the age of Charlemagne to the middle of the ninth century.